2006
DOI: 10.1097/01.ta.0000230567.56797.6c
|View full text |Cite
|
Sign up to set email alerts
|

Local and Distant Burn Injury Alter Immuno-Inflammatory Gene Expression in Skeletal Muscle

Abstract: Burn mediates a common systemic response, independent of the site or extent of injury, and also specific responses to local versus distant trauma. A transcriptome profile of genes that initiate and sustain systemic inflammation has been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
5
12
0
Order By: Relevance
“…This gene encodes for CCAAT/enhancer binding protein delta (CEBPD), a transcription factor that regulates inflammatory and immune responses . The results coincide with those of studies showing overexpression of this gene in sepsis and burn trauma . In addition, CEBPD binds to the IL6 gene promoter and cooperates with nuclear factor–kappaB (NF‐κB) to stimulate maximal transcription of interleukin‐6, a procachectic cytokine …”
Section: Resultssupporting
confidence: 57%
“…This gene encodes for CCAAT/enhancer binding protein delta (CEBPD), a transcription factor that regulates inflammatory and immune responses . The results coincide with those of studies showing overexpression of this gene in sepsis and burn trauma . In addition, CEBPD binds to the IL6 gene promoter and cooperates with nuclear factor–kappaB (NF‐κB) to stimulate maximal transcription of interleukin‐6, a procachectic cytokine …”
Section: Resultssupporting
confidence: 57%
“…The principal findings of the present study are complementary to findings by NMR, suggesting that a major factor in the progression of mitochondrial skeletal muscle dysfunction in burns results from defects in oxidative phosphorylation (OXPHOS) (22)(23)(24)33,34). Indeed, findings with the same mouse 'local' burn model (affecting the hind limb and representing 3-5% of total body surface area) demonstrated that burn injury causes a significant dysregulation in OXPHOS and a decrease in the ATP synthesis rate (23).…”
Section: Discussionsupporting
confidence: 68%
“…Meanwhile, decreased expression of PGC-1ß appears to: a) upregulate UCP3, leading to uncoupling and reduced ATP synthesis rate; and b) alter immuno-inflammatory gene expression in skeletal muscle [in cachexia Fig. 1; in experimental burn injury (31,33,34,36)]. This supposition is in agreement with other studies suggesting that upregulation of mRNA and protein expression of UCP2 and UCP3 (1214) correlates directly with antioxidative capacity (15,16) in response to elevated TNFα-induced ROS production in cancer (60).…”
Section: Discussionmentioning
confidence: 99%